2016
DOI: 10.1242/dmm.025072
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine ameliorates cognitive deficits induced by maternal LPS exposure: A study in rats

Abstract: Maternal exposure to infectious agents is a predisposing factor for schizophrenia with associated cognitive deficits in offspring. A high incidence of smoking in these individuals in adulthood might be, at least in part, due to the cognitive-enhancing effects of nicotine. Here, we have used prenatal exposure to maternal lipopolysaccharide (LPS, bacterial endotoxin) at different time points as a model for cognitive deficits in schizophrenia to determine whether nicotine reverses any associated impairments. Preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 95 publications
3
24
2
Order By: Relevance
“…The data obtained in this study are consistent with our previous research (Waterhouse et al ) and others (Zuckerman & Weiner ). Animals prenatally exposed to MIA showed diminished LI.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The data obtained in this study are consistent with our previous research (Waterhouse et al ) and others (Zuckerman & Weiner ). Animals prenatally exposed to MIA showed diminished LI.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study, we showed that the cognitive deficits induced by MIA were ameliorated after repeated experimenter‐administered NIC (Waterhouse et al ). The findings of the present study extend this to self‐administered NIC.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The team tested the hypothesis that a high incidence of smoking in schizophrenics might be due to the putative cognitive-enhancing effects of nicotine. In support of this effect, the authors found that global cognitive deficits induced by early LPS exposure were at least in part reversed by nicotine treatment in the offspring (Waterhouse et al, 2016). …”
Section: Original Research Contributions: the Uniqueness Of The Rat Mmentioning
confidence: 89%